India's first diplomat V.S. Srinivasa Sastri and the making of liberal internationalism. - THAKUR, VINEET (BRISTOL UNIVERSITY PRESS, 2021)
Though now largely a forgotten figure, V.S. Srinivasa Sastri was a celebrated Indian politician and diplomat in the early 20th Century. This book rehabilitates Sastri and offers a diplomatic biography of his years as India's roving ambassador in the 1920s.